Glycosylated cyclophellitol-derived activity-based probes and inhibitors for cellulases. Issue 3 (28th July 2020) - de Boer, Casper; McGregor, Nicholas G. S.; Peterse, Evert; Schröder, Sybrin P.; Florea, Bogdan I.; Jiang, Jianbing; Reijngoud, Jos; Ram, Arthur F. J.; van Wezel, Gilles P.; van der Marel, Gijsbert A.; Codée, Jeroen D. C.; Overkleeft, Herman S.; et al.
Abstract : New cyclophellitol-derived activity-based probes enable the sensitive detection and identification of cellulases. Abstract : Cellulases and related β-1, 4-glucanases are essential components of lignocellulose-degrading enzyme mixtures. The detection of β-1, 4-glucanase activity typically relies on monitoring the breakdown of purified lignocellulose-derived substrates or synthetic chromogenic substrates, limiting the activities which can be detected and complicating the tracing of activity back to specific components within complex enzyme mixtures. As a tool for the rapid detection and identification of β-1, 4-glucanases, a series of glycosylated cyclophellitol inhibitors mimicking β-1, 4-glucan oligosaccharides have been synthesised. These compounds are highly efficient inhibitors of HiCel7B, a well-known GH7 endo -β-1, 4-glucanase. An elaborated activity-based probe facilitated the direct detection and identification of β-1, 4-glucanases within a complex fungal secretome without any detectable cross-reactivity with β-d -glucosidases. These probes and inhibitors add valuable new capacity to the growing toolbox of cyclophellitol-derived probes for the activity-based profiling of biomass-degrading enzymes.